Predicting outcome in severe ulcerative colitis. Issue 6 (June 1996) - Travis, S P; Farrant, J M; Ricketts, C; Nolan, D J; Mortensen, N M; Kettlewell, M G; Jewell, D P
Abstract : BACKGROUND: Simple criteria are needed to predict which patients with severe ulcerative colitis will respond poorly to intensive medical treatment and require colectomy. AIMS: To find out if the early pattern of change in inflammatory markers or other variables could predict the need for surgery and to evaluate the outcome of medical treatment during one year follow up. PATIENTS: 51 consecutive episodes of severe colitis (Truelove and Witts criteria) affecting 49 patients admitted to John Radcliffe Hospital, Oxford. METHODS: Prospective study monitoring 36 clinical, laboratory, and radiographic variables. All episodes treated with intravenous and rectal hydrocortisone and 14 of 51 with cyclosporine. RESULTS: Complete response in 21 episodes (< or = 3 stools on day 7, without visible blood), incomplete response in 15 (> 3 stools or visible blood on day 7, but no colectomy), and colectomy on that admission in 15. During the first five days, stool frequency and C reactive protein (CRP) distinguished between outcomes (p < 0.00625, corrected for multiple comparisons) irrespective of whether patients or the number of episodes were analysed. It could be predicted on day 3, that 85% of patients with more than eight stools on that day, or a stool frequency between three and eight together with a CRP > 45 mg/l, would require colectomy. For patients given cyclosporine, four of 14 avoided colectomy but two continued to have symptoms. After admission, complete responders remained in remission for a median nine months and had a 5% chance of colectomy. Incomplete responders had a 60% chance of continuous symptoms and 40% chance of colectomy. CONCLUSIONS: After three days intensive treatment, patients with frequent stools (> 8/day), or raised CRP (> 45 mg/l) need to be identified, as most will require colectomy on that admission. The role of cyclosporine for treating severe colitis has yet to be defined. After seven days' treatment, patients with > 3 stools/day of visible blood have a 60% chance of continuous symptoms and 40% chance of colectomy in the following months.